汉印尼语被动句语义对比研究 - susanti susanti (Journal International Lingua Mandarin (JILIN), 2021)
[摘要]汉语是属于藏语系，而印尼语是南岛语系。语系不同，使得汉语被字句和印尼语被动句既有相同之处，也存在很多不同之处。为了帮助印尼汉语学习者更快掌握汉语被字句，提高印尼汉语学习者的汉语水平及翻译能力，因此本文从汉语被字句和印尼语被动句的认知学差异、语义这两个方面进行研究，总结出这两种语言的异同点。 [Abstract] Chinese belongs to the Tibetan language family, while Indonesian is the Austronesian language family. The language family is different, so that Chinese quilt sentences and Indonesian passive sentences have both similarities and many differences. In order to help Indonesian Chinese learners to grasp Chinese quilt sentences faster, and to improve the Chinese proficiency and translation ability of Indonesian Chinese learners, this article studies the cognitive differences and semantics of Chinese quilt sentences and Indonesian passive sentences. Find out the similarities and differences between these two languages.